Positional Isomers of Chromophore–Peptide Conjugates Self‐Assemble into Different Morphologies. Issue 48 (18th July 2018) - Lewandowska, Urszula; Corra, Stefano; Zajaczkowski, Wojciech; Ochs, Nellie A. K.; Shoshan, Michal S.; Tanabe, Junki; Stappert, Sebastian; Li, Chen; Yashima, Eiji; Pisula, Wojciech; Müllen, Klaus; Wennemers, Helma
Abstract: Ordering π‐systems into defined supramolecular structures is important for the development of organic functional materials. In recent years, peptides with defined secondary structures and/or self‐assembly properties were introduced as powerful tools to order peptide–chromophore conjugates into different morphologies. This work explores whether or not the directionality of peptides can be used to control the self‐assembly. The position of the π‐system in conjugates between oligoprolines and perylene monoimide (PMI) chromophores was varied by attaching the PMI moiety to the second‐to‐last residue from the C‐ and N‐termini, respectively. Microscopic and diffraction analysis revealed that the positional isomers form distinctly different supramolecular architectures that extend into the micrometer regime. NMR spectroscopic studies in solution phase allowed correlation of the self‐assembly properties with markedly different conformational preferences of the isomeric building blocks. These insights enabled the design of building blocks with predictable self‐assembly properties. Thus, the directionality of peptides offers exciting opportunities for controlling the self‐assembly and electronic properties of π‐systems. Abstract : "N and C" are not the same : The directionality of the peptide backbone was used to control the formation of different supramolecular architectures that extend into the micrometer regime. The conformational and supramolecular assembly properties of positional isomers of oligoproline–chromophore conjugates were correlated by a combination of spectroscopic, microscopic, and diffraction analyses. This enabled the design of building blocks with predictable self‐assembly properties.